2020
DOI: 10.21203/rs.2.18658/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluations of knowledge, skills and practices of insulin storage and injection handling techniques of diabetic patients in Ethiopian primary hospitals

Abstract: Background: Insulin is an effective therapeutic agent in the management of diabetes, but it is also sensitive to external environment. Consequently, diabetic patients’ adherence to insulin delivery recommendations is critical to its effectiveness. Patients’ lack of knowledge, skill and irrational practices towards appropriate insulin delivery techniques may end up in therapeutic failure and increase costs of therapy. The aim of this study was to evaluate patients’ knowledge, skills and practices of insulin s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This result was in contrast with the study conducted by Netere AK et al, where the mean duration of insulin 2.3 ± 0.8 years. 4 The present study found that most patients lived in rural areas (82.35%), and the rest of the patients lived in urban areas (17.64%). Similar findings were found in the studies conducted by Netere et al, and Mariye T et al, where most patients lived in rural areas (51.8% 7 and 59%, 22…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…This result was in contrast with the study conducted by Netere AK et al, where the mean duration of insulin 2.3 ± 0.8 years. 4 The present study found that most patients lived in rural areas (82.35%), and the rest of the patients lived in urban areas (17.64%). Similar findings were found in the studies conducted by Netere et al, and Mariye T et al, where most patients lived in rural areas (51.8% 7 and 59%, 22…”
Section: Discussionsupporting
confidence: 47%
“…21 The study conducted by Netere AK et al, showed that most of the patients (31.3%) had primary and secondary education. 4 In the present study, the majority of the patients were unemployed. A study conducted by Berhe KK et al, showed that most patients (34.3%) were unemployed.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation